2019
DOI: 10.1055/s-0039-1692442
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association between Inflammation and Ischemic Heart Disease

Abstract: Background Inflammation plays a fundamental role in mediating all stages of atherosclerosis. Given the higher prevalence of inflammatory rheumatologic conditions in women and the female propensity towards worse cardiovascular outcomes, refined strategies are needed to better identify the high-risk female cardiovascular phenotype. Objectives This article aims to assess sex-specific links between inflammatory processes and the development and progression of ischemic heart disease. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
(53 reference statements)
1
18
0
Order By: Relevance
“…A recent study focusing on myocardial function, perfusion, and metabolic amygdalar activity revealed an association between elevated amygdalar activity and impaired myocardial perfusion/function. Notably, these associations were observed in women, but not in men (Fiechter et al, 2019a). Further, resting amygdalar activity was not affected by high coronary artery calcium scoring, suggesting that the extend of myocardial injury, rather than atherosclerotic plaque burden, is mainly responsible for an enhanced neural stress response in the female population.…”
Section: Amygdalar Activity and The Female Heartmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent study focusing on myocardial function, perfusion, and metabolic amygdalar activity revealed an association between elevated amygdalar activity and impaired myocardial perfusion/function. Notably, these associations were observed in women, but not in men (Fiechter et al, 2019a). Further, resting amygdalar activity was not affected by high coronary artery calcium scoring, suggesting that the extend of myocardial injury, rather than atherosclerotic plaque burden, is mainly responsible for an enhanced neural stress response in the female population.…”
Section: Amygdalar Activity and The Female Heartmentioning
confidence: 85%
“…This is a major omission given that experimental studies in rats indicate a twofold higher susceptibility to lethal effects of colchicine in females (Wiesenfeld et al, 2007). While cardiovascular pathologies and outcomes have been associated with a higher level of inflammatory activity, it was only recently demonstrated that an upregulated metabolic activity of the vertebral bone marrow, a surrogate marker of inflammation, is a strong and independent predictor of myocardial injury, suggesting that inflammatory biomarkers play a significant role in the development and progression of CAD toward myocardial ischemia and fibrosis (Fiechter et al, 2019a). Most intriguingly, these observations were sex-dependent with a significant association of inflammation and myocardial function and perfusion in women, but not in men.…”
Section: Altered Autonomous Nervous System Activity and Upregulated Imentioning
confidence: 99%
“…Quantitative myocardial 18 F-FDG uptake was measured by serially placing volumes of interest (VOI) using AW Server software (version 3.2, GE Healthcare) as previously described and validated [ 24 , 25 , 26 , 27 , 28 ]. VOIs were placed as follows: VOI 1 was placed at the mid-ventricular septum, VOI 2 at the anterior apex, VOI 3 at the mid-ventricular lateral wall, VOI 4 basal anterior wall, VOI 5 at the posterior apex, VOI 6 at the liver in an area of low 18 F-FDG uptake, and VOI 7 at the aortic arch.…”
Section: Methodsmentioning
confidence: 99%
“…In their present study, Fiechter et al report from nuclear medicine that for women, a strong association exists between inflammation, as measured by vertebral bone marrow metabolism, and impaired myocardial function and perfusion, as assessed by single photon emission computed tomography-myocardial perfusion imaging (SPECT-MPI). 1 Among a total of 294 patients (28.6% women, mean age 67 years old) who underwent 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography and 99 Tc-tetrofosmin SPECT-MPI, a significant increase in 18 F-FDG bone marrow uptake was observed in women with impaired myocardial perfusion as compared with normal myocardial perfusion (standardized uptake 2.2 AE 1.2 vs. 1.7 AE 1.2, p ¼ 0.013), while no differences were found in men (1.6 AE 0.8 vs. 1.6 AE 0.4, p ¼ 0.372). In addition, a significant inverse correlation between left ventricular ejection fraction and bone marrow metabolism was seen in women (r ¼ -0.229, p ¼ 0.037), but not in men (r ¼ -0.075, p ¼ 0.289).…”
Section: Introductionmentioning
confidence: 99%